Testing the expectations hypothesis of the term structure of interest rates in the presence of a potential regime shift - Markku Lanne (Bank of Finland, 1999)
The expectations hypothesis of the term structure of interest rates is tested using monthly Eurodollar deposit rates for maturities 1, 3 and 6 months covering the period 1983: 1996:6.Whereas classical regression-based tests indicate rejection, tests based on a new model allowing for potential but unrealized regime shifts provide support for the expectations hypothesis.The peso problem is modelled by means of a threshold autoregression.The estimation results suggest that potential regime shift had an effect on expectations concerning the longer-term interest rate only for a short while in the early phase of the sample ??ri?d, when interest rates were at their highest.
URN:NBN:fi:bof-20140807636
Keywords: 330; peso problem; TAR models; term structure of interest rates